LEVERAGING BLOCKCHAIN FOR ESG DISCLOSURE: ENHANCING TRANSPARENCY AND ACCOUNTABILITY IN SUSTAINABILITY REPORTING - Shukla, Tanya (International Journal of Engineering Technologies and Management Research, 2025)
The growing need for Environmental, Social, and Governance (ESG) disclosure accountability and transparency has brought to light serious issues with conventional reporting structures. Problems including data discrepancies, greenwashing, and a lack of real-time verification make ESG disclosures less reliable. With its decentralized and unchangeable ledger, blockchain technology provides a revolutionary answer to these problems. Blockchain increases the legitimacy of ESG reporting by guaranteeing data integrity, improving transparency, and automating compliance through smart contracts. The potential of blockchain technology to overcome current constraints and enhance stakeholder trust is highlighted in this study’s exploration of the technology’s role in ESG disclosure. Several case studies where blockchain has been used to improve the accuracy of ESG data have been analyzed using a descriptive and exploratory research methodology. According to the results, blockchain reduces fraud reporting and expedites verification procedures, which lowers expenses and boosts operational effectiveness. But issues including excessive energy use, unclear regulations, and the requirement for defined ESG criteria continue to be major obstacles to broad implementation. Notwithstanding these obstacles, there are encouraging prospects for more developments in ESG reporting due to the integration of blockchain with cutting-edge technologies like artificial intelligence (AI) and the Internet of Things (IoT). In order to establish a strong framework for blockchain-driven ESG disclosures, this study emphasizes the need for cooperation between regulators, companies, and technology developers. Future studies should concentrate on resolving issues with scalability and creating laws that support the use of blockchain technology in sustainability reporting.